REVERSE EVIDENCE IN CORRUPTION ERADICATION PRACTICE - Sunarto Sunarto; Mochamad Soleh; Nyoman Ardika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
This study aims to determine; 1) law of the evidentiary machine withinside the Criminal Procedure Code and the evidentiary machine withinside the Indonesian Corruption Eradication Law, and 2) synchronization of the reverse evidentiary system regulations in the trial of corruption with human rights of the accused at the trial. This study is a normative legal research with descriptive analysis method. This research shows the results, including: 1) There is a limitation in the system of reversing the burden of proof in Law no. 20 of 2001 regarding Amendments to Law No. 31 of 1999 regarding the Eradication of Corruption Crimes, namely the criminal act of gratification related to bribery in accordance with what is contained in Article 12 B paragraph (1) letter a. The reversal was carried out on the property of the defendant who was allegedly related to the case against which he was charged (Article 37A) and the property of the defendant who was not charged with alleged corruption (Article 38B). 2) In Articles 37A and 38B regarding reversing the weight of evidence at the defendant's property, it's far deemed essential to offer operational commands in addition to unique procedural regulation as an attempt to keep away from ambiguity from regulation enforcement in imposing this system. Afterwards, concerning the reversal of the weight of evidence on items which have now no longer been indicted (Article 3B), the regulation wishes to offer limits and motives concerning the purpose of products which have now no longer been indicted. This makes it necessary to understand what is meant by property in the context found in the trial. However, there has been no indictment allegedly originating from the criminal act of corruption, so it has not yet been delegated to the Public Prosecutor.